Sistem Marketplace Pencarian Lapangan Futsal Menggunakan Metode Haversine Berbasis Android - Muhamad Jamaris; Hendra Saputra; M. Khairul Anam; Khusaeri Andesa; Rahmaddeni Rahmaddeni (STEKOM PRESS, 2022)
Futsal is a soccer game played indoors, this game itself is played by two teams, each team consisting of five people. At this time futsal is very much in demand from various groups ranging from children to adults, so there are many futsal field rental places, especially in the city of Pekanbaru. However, the problem that occurs is that it is still difficult for tenants to find out where there is a futsal field and the nearest futsal field from where the tenant is located, including price information and field facilities. Therefore, we need a system that can make it easier for tenants to find out where there is a futsal field and the nearest futsal field from the tenant's location. This system is made based on Android so that it can make it easier for users to use this system. The method used in making this system is the Haversine method. The results obtained are a marketplace system that can make it easier for users to find out where there is a futsal field, find the nearest field and it is also easy to find out all information related to the field and can make it easier to rent a futsal field through the marketplace system.